2004
DOI: 10.1200/jco.2004.03.132
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Variables and Recurrence Rates As Related to Obesity and Race in Men With Prostate Cancer Undergoing Radical Prostatectomy

Abstract: Obesity is associated with higher grade cancer and higher recurrence rates after RP. Black men have higher recurrence rates and greater BMI than white men. These findings support the hypothesis that obesity is associated with progression of latent to clinically significant prostate cancer (PC) and suggest that BMI may account, in part, for the racial variability in PC risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
259
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 350 publications
(288 citation statements)
references
References 33 publications
22
259
7
Order By: Relevance
“…The investigators suggested that obesity in the African-American population may, in part, underlie the increased prostate cancer risk among African Americans. 6 In our study, the association between ethnicity and either BMI or 2 or greater remained a significant independent predictor of PSA failure. After patients were divided into groups by each 2.5-kg/m 2 separation in BMI, the risk of PSA failure did not dramatically increase until the BMI was 35 kg/m 2 or greater.…”
Section: Resultssupporting
confidence: 47%
See 3 more Smart Citations
“…The investigators suggested that obesity in the African-American population may, in part, underlie the increased prostate cancer risk among African Americans. 6 In our study, the association between ethnicity and either BMI or 2 or greater remained a significant independent predictor of PSA failure. After patients were divided into groups by each 2.5-kg/m 2 separation in BMI, the risk of PSA failure did not dramatically increase until the BMI was 35 kg/m 2 or greater.…”
Section: Resultssupporting
confidence: 47%
“…In a study of 135,000 Swedish construction workers 3 and in two large American Cancer Society cohorts, 11 the prostate cancer mortality rates were consistently greater in patients with a greater BMI, suggesting a greater influence of body mass on prostate cancer aggression, rather than on prostate cancer incidence. 6 Likewise, an analysis from CaPSURE previously found a positive correlation between a greater BMI (Ͼ25 kg/m 2 ) and the risk of being in a worse prognostic group at diagnosis (P ϭ 0.018). 12 It is less clear how obesity affects prostate cancer outcomes after RP.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Few studies focused on this issue. An elevated BMI is a risk factor for the occurrence of several cancers (Moertel et al, 1980;Calle et al, 2003), and is associated with a higher relapse rate after surgical treatment of colon, rectal and prostate cancer (Meyerhardt et al, 2003;Amling et al, 2004;Freedland et al, 2004;Meyerhardt et al, 2004). However, its impact on disease's natural history and response to treatment is less documented.…”
Section: Discussionmentioning
confidence: 99%